1999
DOI: 10.1016/s0008-6363(99)00229-1
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of L-type Ca2+ current in human atrial myocytes by insulin

Abstract: Our data show that insulin stimulates the L-type calcium current in isolated human atrial myocytes in a dose-dependent and reversible manner which appears to involve the insulin receptor tyrosine kinase. Insulin regulation of ICa,L in human atrial myocytes may be an interesting system for the analysis of the metabolic syndrome in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 44 publications
2
27
0
1
Order By: Relevance
“…These data confirm previous reports [4,5], showing an increase in I Ca,L magnitude with insulin (t test; p<0.05). Figures 1c and d show corresponding data at 37°C.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These data confirm previous reports [4,5], showing an increase in I Ca,L magnitude with insulin (t test; p<0.05). Figures 1c and d show corresponding data at 37°C.…”
Section: Resultssupporting
confidence: 93%
“…(f) Steady-state voltage-dependent activation (left) and inactivation (right) curves without (■) or with (■ ■) insulin. Halfmaximal voltage and slope factor values for activation and for inactivation were derived from experiments with protocols shown in insets and were then used to simulate activation and inactivation variables at 2 mV intervals previously [4,5] was attributed to a stimulation of cyclic adenosine monophosphate-dependent protein kinase. Clearly, the pathways responsible for the inhibitory effect of insulin on I Ca,L at 37°C must now be elucidated.…”
Section: L-type Ca2+ Current (Ical) Measurementmentioning
confidence: 99%
“…Impaired activity of insulin receptor tyrosine kinase has been shown in a variety of tissues from insulin-resistant subjects. Therefore, we hypothesized that insulin action on I Ca,L is mediated by the insulin receptor (IR) and insulin receptor tyrosine kinase involving the adenylyl cyclase/ cAMP/protein kinase A (PKA)-second messenger pathway [2].…”
Section: Dear Sirmentioning
confidence: 99%
“…We have previously shown that insulin stimulates I Ca,L in rat ventricular and human atrial cardiomyocytes in a dose-dependant and reversible manner at concentrations of 100 nmol/l, 1 mmol/l and 10 mmol/l. Maximal stimulation of I Ca,L was obtained at 10 mmol/l of insulin.Furthermore, insulin stimulation leads to an increase in cellular cyclic adenosine-monophosphate (cAMP) content and insulin-induced I Ca,L stimulation can be precluded by tyrosine kinase (IRTK) inhibition [1,2]. Impaired activity of insulin receptor tyrosine kinase has been shown in a variety of tissues from insulin-resistant subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation